2005
DOI: 10.1007/s11167-005-0579-2
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Urea with Citric Acid

Abstract: Reaction of urea with citric acid in aqueous solutions at molar ratios of 1 : 1, 1 : 2, and 2 : 1 and the solubility of urea citrate were studied. The data obtained can serve to optimize use of citric acid as a physiologically active substance or nitrification inhibitor and in production of liquid fertilizers containing urea.Urea is a frequent component of many liquid integrated fertilizers. Interaction of urea with citric acid can affect phase equilibria in the systems constituting liquid complex fertilizers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 3 publications
(2 reference statements)
2
9
0
Order By: Relevance
“…However, the crosslinking of chitosan through the interaction of its amino groups with EDTA is possible, since EDTA is a tetra functional acid. The protonation of urea by organic acids resulting in compounds of varying stoichiometry and structure has also been reported (Paleckiene, Sviklas, & Slinksiene, 2005;Radell, Brodman, & Domanski, 1967). Thus, the reaction between urea and citric acid is reported to result in the formation of urea citrate (with a molar ratio 1:1).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the crosslinking of chitosan through the interaction of its amino groups with EDTA is possible, since EDTA is a tetra functional acid. The protonation of urea by organic acids resulting in compounds of varying stoichiometry and structure has also been reported (Paleckiene, Sviklas, & Slinksiene, 2005;Radell, Brodman, & Domanski, 1967). Thus, the reaction between urea and citric acid is reported to result in the formation of urea citrate (with a molar ratio 1:1).…”
Section: Resultsmentioning
confidence: 90%
“…The presence of some of the prominent peaks from EDTA (see the characterization data pertinent to EDTA blank or control reaction as well as unreacted EDTA in Supplementary Data) and urea (see the characterization data pertinent to urea blank or control reaction as well as unreacted urea in Supplementary Data) as well as new peaks in the product confirmed that a reaction had taken place between urea and EDTA. This was not surprising considering that organic acids are known to react with urea (Paleckiene et al, 2005).…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, heating urea and citric acid in the presence of sulfuric acid uracil-acetic acid is formed [494]. The citric acid-urea system was also investigated by Paleckiene et al [603], but in the context of liquid fertilizers containing urea and the influence of citric acid on corresponding phase equilibria. It was observed by Brettle [604] that citric acid reacts with chloral Cl 3 CCHO, to give citric acid chloralide (actually, from condensation of citric acid with chloral hydrate in concentrated sulfuric acid).…”
Section: Formation Of Amides Citrate-based Siderophores and Other Commentioning
confidence: 99%
“…Afterwards, the compressive strength was decreased to (12.84 MPa) as in the HAC3 composite as a result of the reduction of interaction between two matrices. The values of compressive strength of all HAC composites were higher than that of the prepared HA (9.66 MPa) proving the role of chitosan polymer matrix in enhancement of the bonding strength between the HA particles within the composite (14) . The compressive strength of the HAC/citric acid composites increased especially in the case of HAC2/citric acid composite recording 30.5 MPa in comparison with the HAC composites.…”
Section: Tga Analysismentioning
confidence: 79%
“…at 1028, 603 and at 569 cm -1 were reduced compared to the original bands in the HA powder proving the coating effect, especially in the case of the HAC2 composite. Also, the bands of chitosan in the spectra of HAC composites such as OH at 3446 cm -1 , CH at 2921 cm -1 and amide I at 1652 cm -1 were reduced compared to original polymer denoting interactions through hydrogen bonds as follows: (1) The OH of HA and chitosan, (2) the calcium of the HA with OH or amino group of chitosan, (3) the phosphate of the HA with the amino group of chitosan (14) .…”
Section: Sample Characterizationmentioning
confidence: 98%